Methodological Features of GDP Formation Within the Framework of the System of National Accounts - K. A. Alekseev (Статистика и экономика, 2020)
Purpose of the study. The aim of this work is to examine methodological approaches to the formation of gross domestic product on an annual and quarterly basis within the framework of the System of National Accounts, using the example of 189 countries. The work is based on a dynamic and structural analysis of statistical information of gross domestic product published on the official websites of statistical agencies and the International Monetary Fund.Materials and methods. The information base of the study is the official statistical data of countries published on the website of the International Monetary Fund, as well as methodological provisions for the formation of gross domestic product. The research methodological base is represented by statistical methods of information analysis and empirical research.Results. The analysis of data and methodological approaches to gross domestic product formation in different countries has been carried out, as a result of which the main problems of a number of countries regarding the accuracy and relevance of gross domestic product data have been identified. These problems are grouped into six key criteria based on practical macroeconomic approaches, in particular gross domestic product: updating of the base year, annual and quarterly gross domestic product data, timeliness of reporting gross domestic product data, method of compiling gross domestic product (production, expenditure, income), use of the international standard “System of national accounts, 2008”.Conclusion. Despite a rather large volume of macroeconomic indicators, one of the main indicators is gross domestic product, the dynamics of which reflects the development of the economy. Therefore, reliable data on gross domestic product play a key role in the analysis of macroeconomic and financial policies, as well as in the analysis and accuracy of forecasting the development of the country’s economy. The study revealed that 50% of the countries surveyed had acceptable base years, meaning that the transition to the new base year did not exceed 10 years. Virtually all countries generate annual gross domestic product data, while quarterly estimates of gross domestic product form about 65% of countries. The timeliness of data dissemination also varies from country to country, and many do not publish date information. 72% surveyed countries provide annual gross domestic product data in a timely manner, while 55% surveyed countries provide quarterly gross domestic product data in a timely manner. The production method is the most common of the three methods of calculating gross domestic product (the production method, the method of using income and the generation of gross domestic product by source of income). Gross domestic product formation in accordance with the current version of the international standard “System of National Accounts, 2008” is applied in 52% of countries, and in most other countries the previous version of the international standard “System of National Accounts, 1993” is used.